Numerical solution of an eigenvalue problem for bounded plasma (2011)
This article is the result of a research on the propagation of electromagneticwaves in a plasma found confined in a cylindrical metal structure through an intenseaxial magnetic field. The eigenvalue problem resulting from this study is numericallysolved and frequencies of the first electromagnetic modes are obtained. Results ofthis work could be applied to characterize plasmas at the laboratory.